1998
DOI: 10.1080/03014223.1998.9518155
|View full text |Cite
|
Sign up to set email alerts
|

Prey‐capture techniques and prey preferences of nine species of ant‐eating jumping spiders (Araneae: Salticidae) from the Philippines

Abstract: Siler sp., Euophrys sp. 1 and 2, and six species of Chalcotropis feed on ants in nature. Capture techniques and preferences of each species were studied in the laboratory using a wide variety of ants and other insects. Siler sp. usually attacked ants, but not other insects, from directly behind. Euophrys sp. 1 and 2 consistently attacked ants, but not other insects, head on. Chalcotropis attacked large ants head on, but there was no particular orientation of attacks on small ants or on other prey regardless of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…Influence of hunger on strength of preference When well-fed (i.e., after a fast of only 1 week), the three species of Zenodorus, along with the other 21 myrmecophagic species that have been studied (Jackson & van Olphen 1991, 1992Jackson et al 1998;Li et al 1996Li et al , 1999, showed consistent preference for ants over other insects in three types of tests. Like prey-specific capture behaviour, the preferences of these species appear to be preprogrammed (i.e., preference did not depend on prior experience with ants).…”
Section: Specialisation In Myrmecophagic Salticidsmentioning
confidence: 99%
See 4 more Smart Citations
“…Influence of hunger on strength of preference When well-fed (i.e., after a fast of only 1 week), the three species of Zenodorus, along with the other 21 myrmecophagic species that have been studied (Jackson & van Olphen 1991, 1992Jackson et al 1998;Li et al 1996Li et al , 1999, showed consistent preference for ants over other insects in three types of tests. Like prey-specific capture behaviour, the preferences of these species appear to be preprogrammed (i.e., preference did not depend on prior experience with ants).…”
Section: Specialisation In Myrmecophagic Salticidsmentioning
confidence: 99%
“…Zenodorus durvillei, Z. metallescens and Z. orbiculatus, along with 21 species previously studied (Edwards et al, 1974;Cutler 1980;Jackson & van Olphen 1991, 1992Jackson et al 1998;Li et al 1996Li et al ,1999, appear to be exceptions to the rule that salticids are averse to ants as prey (Bristowe 1941). "Myrmecophagic" is an appropriate term for these 24 species.…”
Section: Specialisation In Myrmecophagic Salticidsmentioning
confidence: 99%
See 3 more Smart Citations